A inserção de tópicos de física de partículas no Ensino Médio utilizando a técnica scale-up - Medeiros, Larissa Veríssimo de (2022)
The presence of Information and Communication Technologies (ICT) in the students' daily routine is notorious, as digital natives, they resort to the use of digital media as required. On the other hand, the insertion of Modern Physics in the classroom also presents obstacles in adapt the technical language to an accessible format and in the feasibility of this theme in the curriculum. Therefore, it is important to use teaching approaches allied to technologies seeking to facilitate the understanding of Modern Physics. In this context, breaking with a student potential passivity is a possibility for incorporating ICT into Modern Physics teaching, and as an alternative to traditional teaching method, the active methodologies were developed to enable the active involvement of students in the learning process. Among the methodologies available, the Student-Centered Active Learning Environment with Upside-down Pedagogies (SCALE-UP), developed for Higher Education, stands out as a transformational technique for the classroom environment. Integrated to the use of the flipped classroom, SCALE-UP seeks to promote stimulation and engagement through interaction between students and teachers. Pursuing ways to develop an implementation of particle physics in the context of hybrid education classroom using the SCALE-UP technique, we developed a teaching sequence in a 2nd year high school class in a private educational institution in the city of João Pessoa in Paraíba. The teaching sequence was developed in four meetings with a total of 850 hours and the participation of students in discussions and tasks inside and outside the classroom stands out, which generated results in the form of an experience report, demonstrating how the SCALE-UP technique was an important tool in transforming the dynamics of the class, as well as in the attitude and involvement of students in the learning process, making them reflect on each task in a more critical and participatory way. The research also detected an improvement in student motivation and in the frequency of delivery activities, corroborating the relevance of using the SCALE-UP technique. In view of these results, it is concluded that SCALE-UP is a technique that can be applied to Basic Education and adapted to the needs and reality of each institution.